Laser scanning and creation of a bim model of the building No. 1 NTUU “Igor Sikorsky KPI” as a method of visualizing historical and architectural heritage - Kovalchuk, I.; Kozhemiako, M.; Kozhemiako, P.; Kutsenko, O.; Matviichuk, D. (Land Management, Cadastre and Land Monitoring, 2025)
The article describes a comprehensive approach to obtaining and processing data after terrestrial laser scanning of an architectural monument and creating a BIM model of a fragment of the facade of a historic building – the First Building of the Igor Sikorsky Kyiv Polytechnic Institute. In the course of this work, modern methods of spatial fixation of the object under study were used, including high-precision 3D scanning with a Leica ScanStation C10 scanner, point cloud registration, data filtering, and the results of their further processing in Leica Cyclone REGISTER 360 and Autodesk ReCap software, and the construction of an informational 3D model of this building in the Autodesk Revit environment. Foreign and domestic experience in performing such work has been analyzed. It has been shown that one of the most effective methods of spatial documentation is terrestrial laser scanning (TLS), which provides a high-precision point cloud that reflects the actual shape of an object with an accuracy of several millimeters. International studies show that Scan-to-BIM technology is key in the processes of digital restoration and planning of reconstructions of historical objects. It is noted that Ukraine lacks systematic applied research that would combine these technologies into a comprehensive algorithm for specific historical and architectural objects. This circumstance indicates the practical importance of this research and the need for further development of methods for documenting historical facades using modern geodetic and geoinformation technologies. The article pays particular attention to ensuring high data accuracy, station registration algorithms, scan parameter selection, and the potential for further use of the model in restoration work, technical condition monitoring, and digital conservation of cultural heritage objects. The LOD 300 model confirms the possibility of high-quality reproduction of the geometry of historical objects using Scan-to-BIM technology in the Ukrainian context. Keywords: terrestrial laser scanning, point cloud, TLS, BIM model, Scan-to-BIM, digital preservation, historic building, architectural heritage, Autodesk Revit, Leica ScanStation C10, point cloud registration, Cyclone REGISTER 360, HBIM, facade restoration, 3D modeling, geodetic documentation, information modeling, measurement accuracy, LOD 300, digital reconstruction.